A Novel Dressing for Wound Care Based on Konjac Glucomannan - Mashudi, Sugeng; T.N. Saifullah; Handoko, Lukman; Aldi Purnomo, Rochmad (The SDGS Forum Communication, 2024)
Wound management has become a crucial component of healthcare systems since wound healing continues to be a problem for the nursing sciences. One area that could provide novel methods for regenerative complementary nursing is konjac glucomannan. It is necessary to emphasize the significance when konjac glucomannan is incorporated into biomaterials, it may induce particular qualities that make the biomaterials more effective. They are appealing as wound dressing materials. In this review, we will talk about the first line of bioactive konjac glucomannan-based dressings that are often used in nursing practice. These include semipermeable films, hydrogel dressings, hydrocolloid dressings, alginate dressings, non-adherent contact layer dressings, and multilayer dressings. This review will also point out that there isn'tenough high-quality evidence and that more advanced trials need to be done because most current wound healing treatments don't work well, either structurally or functionally. Konjac glucomannan is a unique tool that can be used to help heal wounds. They can be made to closely resemble the natural processes that lead to tissue repair.